examination of the effects of liraglutide on diabetic nephropathy - Akihiro Ryuge; Kusama Minoru; Kouchi Yu; Ozeki Takaya; Yazawa Masahiko; Yamaguchi Makoto; Ohyama Yukako; Haji Yoichiro; Imaizumi Takahiro; Tomino Tatsuhito; Shimizu Hideaki; Nakashima Eitaro; et al. (The Korean Society of Nephrology, 2012)
Liraglutide (Lira), a glucagon-like peptide-1 receptor agonist, can be administered to diabetic patients with renal failure without dose reduction, but experience with the use of Lira in these patients is limited. This study was designed to examine the effects of 6-month Lira administration on glucose metabolism, body mass index (BMI), and renal function in 18 patients with diabetic nephropathy (eGFR <60 ml/min). The study included 18 patients with diabetic nephropathy who were on insulin/oral hypoglycemic medications (6 men, 12 women; average age, 60 years; HbA1c, 8.4%; BMI, 29.4 ± 8.2; duration of diabetes, 12 years; eGFR, 55.2 ± 6.3 ml/min/1.73 m2). Lira was given either in combination or as monotherapy. After 6 months of Lira treatment, changes in HbA1c levels, casual blood glucose levels, BMI, and eGFR were examined. The average HbA1c and casual blood glucose levels were significantly decreased after 6-month Lira administration (HbA1c before administration 8.4%, 7.9% at Month 1, 7.4% at Month 2, 7.1% at Month 3, 7.1% at Month 6; p < 0.01 respectively, Paired T test). There were, however, no significant changes in renal function. In conclusion, these results suggest that the administration of Lira in patients with diabetic nephropathy may improve glucose metabolism and reduce BMI without affecting renal function or albuminuria in the short term.